Compatibility study of Trichoderma sp. with Chemical Fungicides Commonly Used by Nepalese Farmers, Under In-Vitro Condition - Poudel, Sudeep; Pun, Lok Bahadur; Paudel, Rajan; Pokharel, Sadikshya; Khanal, Pratit (Hasanuddin University, 2024)
The excessive use of synthetic fungicides has led to the emergence offungicide-resistant strains of pathogens, raising concerns about human health andenvironmental impact. Trichoderma spp., an endophytic and versatileopportunistic plant symbiont, has recently gained popularity as a biocontrolagent. Integrated use of Trichoderma with compatible fungicides gives betterdisease management and causes less harm to the environment in the long run.This study aimed to evaluate the compatibility of six fungicides commonly used byNepalese farmers at concentrations of 250, 500, and 1000 ppm with Trichodermasp. using the poisoned food technique in-vitro. The experiment was conducted ina completely randomized design with four replications for each treatment, anddata were taken at 24, 36, 48, 60, and 72 hours after incubation. Among thefungicides tested, Mancozeb was compatible at all concentrations from the startand exhibited the highest compatibility at 72 hours, with a growth inhibitionpercent of 0.39%. Metalaxyl+Mancozeb at 250 and 500 ppm, and Copperoxychloride at 250 ppm showed good compatibility. However, Carbendazim,Hexaconazole, and Carbendazim+Mancozeb resulted in 100% growth inhibition ofTrichoderma sp. throughout the experiment. While all treatments significantlyreduced mycelial diameter, Mancozeb and Metalaxyl+Mancozeb showed agradual decrease in growth inhibition percent over time, indicating increasedcompatibility. In contrast, Copper oxychloride demonstrated variable growthinhibition percent over time. So, the fungicides Mancozeb, Metalaxyl+Mancozeband Copper oxychloride at compatible concentrations can be used withTrichoderma sp. in integrated disease management to control soil and seed-bornepathogens.